Variation in the functional meaning of radicalization - Essra Jawad Alebadi (Tikrit Journal For Political Science, 2025)
Extremism is a psychological and social phenomenon with political, religious and societal impacts, and has negative consequences and results on all societal areas due to the emergence of a set of unacceptable behaviors. The concept of extremism is also one of the concepts that are difficult to define, and this stems from the orientations and qualitative concepts that are related to individuals, their societal orientations, their personal experiences and their prior assessment of individual and collective preferences. The linguistic meaning of extremism refers to the excess in relative moderation, in addition to belonging that differs from one society to another according to the differences, trends and standards specified for it. Extremism is a relative and disputed expression that has not received an agreed-upon global conceptual orientation. It is used to describe ideas or actions that are viewed by those who issue this expression as unjustified in terms of ideas. This expression is used to stigmatize political ideology that is considered far from the political orientation of society. From a political perspective, it describes the extremist economic orientation stemming from the imposition of strict economic policies. From a social perspective, extremism is linked to social identity, and from a religious perspective, it is linked to religious interpretation that is far from moderation. Many attempts have emerged to confront extremism in all its forms by states and civil society institutions by creating rehabilitation centers and rebuilding individuals’ thinking in a manner that is consistent with the requirements of peaceful societal coexistence. However, they face many challenges, including the negative view (societal stigma), self-inhibitions, poverty, marginalization, and societal exclusion based on inequality, which makes the individual lose his sense of identity and national belonging.